Implementation of the Prophecy Program of the Indonesian Ulama Council (MUI) Medan City - Ayu Amamah; Ahmad Tamrin Sikumbang (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study was conducted to analyze the extent to which the MUI Medan City da'wah program has been implemented. The purpose of this study is to determine how the implementation of the da'wah program is carried out by the Indonesian Ulema Council (MUI) of Medan City. The research method used is a qualitative descriptive approach, where data collection is carried out through observation, interviews, and documentation. The data used in this study consists of primary and secondary data. The main informant used as the primary data source is the Chairperson of the Dakwah and Community Development Commission of the MUI Medan City. Meanwhile, secondary data was obtained from documentation, archives, and other sources. The results of the study indicate that there are two types of da'wah programs implemented, namely direct da'wah activity implementation programs and da'wah activity implementation programs through social media. The implementation of the da'wah program by the MUI Medan City shows positive results and is in accordance with the established program standards.